The frozen river [compact disc, unabridged] - Lawhon, Ariel (Penguin Random House Audio Publishing, 2024)
Maine, 1789: When the Kennebec River freezes, entombing a man in the ice, Martha Ballard is summoned to examine the body and determine cause of death.